Transisi New Normal: Bagaimana Masyarakat Rural dapat Bertahan? - Pratiwi Nurhabibi; Rahmadhona Fitri Helmi; Iip Permana; Fajar Ruddin; Boni Saputra (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The Indonesian government has declared a new order to live side by side with COVID-19, through the idea of a